Skrining Berbagai Jenis Surfaktan Dan Kosurfaktan Sebagai Dasar Pemilihan Formulasi Nanoemulsi - Nirmalayanti, Ni Luh Putu Karunia Vidya (Jayapangus Press, 2021)
The main components for making nanoemulsions are oil, surfactants, and cosurfactants. Before formulating nanoemulsions, screening the surfactants and cosurfactants is necessary to produce an optimum formula. Thus, it carries out surfactants screening, namely (tween 20, tween 60, tween 80) and cosurfactants (propyleneglycol, PEG 400, glycerin). This study aimed to screen suitable selection and cosurfactants as the basis for making nanoemulsions. Then, the research method was carried out in two ways: surfactant screening and cosurfactant screening. The final results were analyzed using a pseudoternary phase diagram. The surfactant screening results were tween 20 (40mL), tween 60 (40mL), tween 80 (60mL); thereby, the best surfactant candidate was tween 80. The results of the surfactant screening on the pseudoternary phase diagram are the most optimal, namely tween 80 with propylene glycol because it has a large nanoemulsion formation area. The study proposed the ratio of oil: smix (tween 80 and propyleneglycol) (1:9) as the optimum formula used to make a nanoemulsion base.